Learn how to program with Java (Addison-Wesley Professional, 2022)
7+ Hours of Video Instruction Overview Learn How to Program with Java LiveLessons takes the learner from beginner to proficient, covering all the important concepts in Java: from basic syntax, to object-oriented basics, to using libraries, to building user interfaces. Description The Java programming language is designed specifically to be readable, secure, and highly performant; therefore, small and large companies make use of it, and knowing Java guarantees you a variety of career options for the foreseeable future. Becoming an effective Java programmer requires much more training than learning languages such as Python or JavaScript. In this course, Shaun bridges the gap and provides students with all the resources they need to effectively program in Java. This course provides a solid foundation in programming with Java. Shaun starts off teaching the basics, such as data types, basic syntax, and program structure with simple operations. He then moves into the basics of object-oriented programming in Java, then into more granular topics, such as mapping and user interfaces. About the Instructor Shaun Wassell is a senior software developer who specializes in full-stack development and software architecture. He manages teams of developers and teaches hundreds of thousands more how to create enterprise-ready applications. Shaun's online courses have more than 300,000 learners, largely because of his passion for development and his focus on helping people apply their programming skills in the real world. He is a lifelong programmer and problem-solving addict whose goal is to help people solve meaningful problems by mastering the art of software development. Please don't hesitate to get in touch with him about any opportunities or if you'd like to stay up to date on his other courses and live trainings. Skill Level Beginner What You Will Learn The art of thinking like a programmer The basics of Java in a fun and hands-on way Object-oriented programming and how it works, with many examples How to build user interfaces with Java's Swing library How to use Java Collections to work with data effectively How to run multiple operations at the same time in Java Deployment options for Java applications Who Should Take This Course Junior developers Mid-level developers Course Requirements This is an entry-level course, so there are no mandatory prerequisites. Some existing knowledge of basic programming concepts might be helpful but is not necessary. About Pearson Video Training Pearson publishes expert-led video tutorials covering a wide selection of technology topics designed to teach you the skills you need to succeed. These professional and personal technology videos feature world-leading author instructors published by your trusted technology brands: Addison-Wesley, Cisco Press, Pearson IT Certification, Sams, and Que. Topics include IT Certification, Network Security, Cisco Technology, Programming, Web Development, Mobile Development, and more. Learn more about Pearson Video training at http://www.informit.com/video.